1997
DOI: 10.1182/blood.v90.3.967
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With a New Synthetic Retinoid, Am80, of Acute Promyelocytic Leukemia Relapsed From Complete Remission Induced by All-trans Retinoic Acid

Abstract: Differentiation therapy with all-trans retinoic acid (ATRA) has marked a major advance and become the first choice drug in the treatment of acute promyelocytic leukemia (APL). However, patients who relapse from ATRA-induced complete remission (CR) have difficulty in obtaining a second CR with a second course of ATRA therapy alone. We tested the efficacy of a new synthetic retinoid, Am80, in APL that had relapsed from CR induced by ATRA in a prospective multicenter study. Am80 is approximately 10 times more pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…Furthermore, the episodes of APL differentiation syndrome were both non-severe and manageable. Tobita et al (1997) have also reported on the use of tamibarotene in the relapsed setting. In their trial, 24 patients with APL who relapsed after ATRA-containing treatment were treated with tamibarotene alone (6 mg/m 2 /d).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the episodes of APL differentiation syndrome were both non-severe and manageable. Tobita et al (1997) have also reported on the use of tamibarotene in the relapsed setting. In their trial, 24 patients with APL who relapsed after ATRA-containing treatment were treated with tamibarotene alone (6 mg/m 2 /d).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently dramatic results have been achieved with the use of arsenic compounds such as AS 2 O 3 ( Shen et al , 1997 ); although experience with these agents is fairly limited to date and as they are not yet widely available their optimal place in the management plan remains to be established. There has also been considerable interest in alternative retinoid differentiating agents to ATRA, including 9‐ cis RA ( Fenaux et al , 1997 ) and synthetic retinoids such as Am80 ( Tobita et al , 1997 ), in the hope that they would circumvent problems with retinoid resistance. However, in the present report we describe the use of ATRA in two children with relapsed APL which was successful despite its prior inclusion as a component of the original induction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…CD38 probably plays an important role in the development of RAS [6], observed during differentiation-inducing therapy for APL by ATRA, with extensive infiltration of myeloid cells into organs, including lungs, skin, kidneys, liver, and LNs [21][22][23]. RAS was also observed during differentiation therapy by tamibarotene [24]. Based on data of AML M3 NB4 cells in this study, it is predicted that the incidence rate of RAS between ATRA and tamibarotene may not be different.…”
Section: Discussionmentioning
confidence: 99%